APA Handbook of Industrial and Organizational Psychology, Vol 3: Maintaining, Expanding, and Contracting the Organization. 2011
DOI: 10.1037/12171-001
|View full text |Cite
|
Sign up to set email alerts
|

Person–environment fit.

Abstract: Of all the issues in psychology that have fascinated scholars and practitioners alike none has been more pervasive than the one concerning the fit of person and environment. (B. Schneider, 2001, p. 141) Person-environment fit is defined as the compatibility that occurs when individual and work environment characteristics are well matched (Kristof-Brown, Zimmerman, & Johnson, 2005). Models of personenvironment (PE) fit have always been a prominent theme in the field of industrial and organizational psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
367
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(418 citation statements)
references
References 261 publications
(546 reference statements)
19
367
0
7
Order By: Relevance
“…Despite the many studies on P-E fit, scholars have mostly focused on the outcomes but not on the antecedents of fit, although several theoretical accounts have been made on development of fit, including the attractionselection-attrition model, socialization, and interpersonal interactions (Kristof-Brown & Guay, 2011). In the present study, we isolate the positive affect shared among members as a potential predictor of group-level fit.…”
mentioning
confidence: 88%
“…Despite the many studies on P-E fit, scholars have mostly focused on the outcomes but not on the antecedents of fit, although several theoretical accounts have been made on development of fit, including the attractionselection-attrition model, socialization, and interpersonal interactions (Kristof-Brown & Guay, 2011). In the present study, we isolate the positive affect shared among members as a potential predictor of group-level fit.…”
mentioning
confidence: 88%
“…The Distinctiveness measure was adapted from the 4-items used by Griepentrog et al (2012), who found this scale to indicate adequate reliability (α = .75) and also demonstrate a positive relationship with group identification. Perceived fit was measured with the 3-item measure developed by Cable and DeRue (2002), which is one of the most common fit measures and generally indicates high reliability scores (Kristof-Brown & Guay, 2011). Each item was measured on a 7-point Likert-type scale.…”
Section: Methodology Sample and Measuresmentioning
confidence: 99%
“…The consideration concerning the person-environment being well matched is based on a tradition about interaction in the field of psychology declaring that individuals' behavior is a function of their characteristics and the environment where they do their activities [13]. The person-environment relation becomes compatible when individuals' perception is well matched with the characteristics of the work environments are desired [14]. Person-environment naturally influence to each other of being reciprocally [15] [12].…”
Section: Introductionmentioning
confidence: 99%